R&D Investments in Plant Breeding under Changing Intellectual Property Rights - Arzandeh, Mehdi; Brewin, Derek G. (International Journal of Economics and Financial Issues, 2021)
In a Cournot duopoly model, we examine three policy regimes relevant to current international plant breeding: patents alone, patents with a farmer exemption to use saved seed, and patents with research collaboration. In the symmetric version of the model where firms are identical, we show that the social planner prefers patents with research collaboration over patents alone and prefers the patents alone to patents with a farmer exemption. We examine two variations of the model where firms are asymmetric i. due to cost differences and ii. due to the different endowments of germplasm. Situations develop where the research collaboration resolves the common pool problem and increases R&D investment and where it creates free riding problem and decreases R&D investment. We show that the lower cost (more endowed) breeder invests more in R&D under the research collaboration than patents if variety differentiation is high and cost (knowledge endowment) dispersion is low. On the other hand, the higher cost (less endowed) breeder, generally, invests less in R&D under a research collaboration if variety differentiation or cost (knowledge endowment) dispersion is low. These findings suggest new gains are likely from the adoption of international conventions of plant breeders' rights. Keywords: Plant breeding, farmer exemption, research collaboration, Intellectual Property Rights, product differentiation, Cournot oligopoly. JEL Classifications: D21, D43, D60, D82, L13, L24, O34, O38, Q16, Q18 DOI: https://doi.org/10.32479/ijefi.11544